High-Precision Optical Coherence Tomography Navigated Laser Retinopexy for Retinal Breaks - Simon Salzmann; Philip Wakili; Sami Al-Nawaiseh; Boris Považay; Christoph Meier; Christian Burri (Life, 2023)
The prevalent cause of retinal detachment is a full-thickness retinal break and the ingress of fluid into the subretinal space. To prevent progression of the detachment, laser photocoagulation (LPC) lesions are placed around the break in clinical practice to seal the tissue. Unlike the usual application under indirect ophthalmoscopy, we developed a semi-automatic treatment planning software based on a sequence of optical coherence tomography (OCT) scans to perform navigated LPC treatment. The depth information allows demarcation of the border where the neurosensory retina is still attached to the retinal pigment epithelium (RPE), which is critical for prevention of detachment progression. To evaluate the method, artificially provoked retinal breaks were treated in seven ex-vivo porcine eyes. Treatment outcome was assessed by fundus photography and OCT imaging. The automatically applied lesions surrounding each detachment (4.4–39.6 mm2) could be identified as highly scattering coagulation regions in color fundus photography and OCT. Between the planned and applied pattern, a mean offset of 68 µm (SD ± 16.5 µm) and a mean lesion spacing error of 5 µm (SD ± 10 µm) was achieved. The results demonstrate the potential of navigated OCT-guided laser retinopexy to improve overall treatment accuracy, efficiency, and safety.